Advance waterway transport system based on Internet of Things (IoT) - Miah, MD Imtiaj; Gope, Joy Chandra; Nath, Ananta Deb; Nain, A.K.M. Janaite; Mitu, Faria Nasir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.